Samacheer Kalvi 9th Maths Chapter 3 Algebra Notes PDF Download: Tamil Nadu STD 9th Maths Chapter 3 Algebra Notes 
Samacheer Kalvi 9th Maths Chapter 3 Algebra Notes PDF Download: Students of class can download the Samacheer Kalvi 9th Maths Chapter 3 Algebra Notes PDF Download from our website. We have uploaded the Samacheer Kalvi 9th Maths Chapter 3 Algebra notes according to the latest chapters present in the syllabus. Download Samacheer Kalvi 9th Maths Chapter 3 Algebra Chapter Wise Notes PDF from the links provided in this article.
Samacheer Kalvi 9th Maths Chapter 3 Algebra Notes PDF Download
We bring to you specially curated Samacheer Kalvi 9th Maths Chapter 3 Algebra Notes PDF which have been prepared by our subject experts after carefully following the trend of the exam in the last few years. The notes will not only serve for revision purposes, but also will have several cuts and easy methods to go about a difficult problem.
Board 
Tamilnadu Board 
Study Material 
Notes 
Class 
Samacheer Kalvi 9th Maths 
Subject 
9th Maths 
Chapter 
Chapter 3 Algebra 
Format 

Provider 
How to Download Samacheer Kalvi 9th Maths Chapter 3 Algebra Notes PDFs?
 Visit our website  https://www.samacheerkalvibook.com/
 Click on the Samacheer Kalvi 9th Maths Notes PDF.
 Look for your preferred subject.
 Now download the Samacheer Kalvi 9th Maths Chapter 3 Algebra notes PDF.
Download Samacheer Kalvi 9th Maths Chapter 3 Algebra Chapterwise Notes PDF
Students can download the Samacheer Kalvi 9th Maths Chapter 3 Algebra Notes PDF from the links provided in this article.
Tamilnadu Samacheer Kalvi 9th Maths Solutions Chapter 3 Algebra Additional Questions
Exercise 3.1
Question 1.
Classify the following polynomials based on number of terms.
(i) x^{3} – x^{2}
(ii) 5x
(iii) 4x^{4} + 2x^{3} + 1
(iv) 4.x^{3}
(v) x + 2
(vi) 3x^{2}
(vii) y^{4} + 1
(viii) y^{20} + y^{18} + y^{2}
(ix) 6
(x) 2u^{3} + u^{2} + 3
(xi) u^{23} – u^{4}
(xii) y
Solution:
5x, 3x^{2}, 4x^{3}, y and 6 are monomials because they have only one term.
x^{3} – x^{2}, x + 2, y^{4} + 1 and u^{23} – u^{4} are binomials as they contain only two terms.
4x^{4} + 2x^{3} + 1 , y^{20} + y^{18} + y^{2} and 2u^{3} + u^{2} + 3 are trinomials as they contain only three terms.
Question 2.
Classify the following polynomials based on their degree.
Solution:
p(x) = 3, p(x) = 7, p(x) = 32 are constant polynomials
p(x) = x + 3, p(x) = 4x, p(x) = 3–√x + 1 are linear polynomials, since the highest degree of the variable x is one.
p(x) = 5x^{2} – 3x + 2, p(y) = 52 y^{2} + 1, p(x) = 3x^{2} are quadratic polynomials, since the highest degree of the variable is two.
p(x) = 2x^{3} – x^{2} + 4x + 1, p(x) = x^{3} + 1, p(y) = y^{3} + 3y are cubic polynomials, since the highest degree of the variable is three.
Question 3.
Find the product of given polynomials p(x) = 3x^{3}+ 2x – x^{2} + 8 and q (x) = 7x + 2.
Solution:
(7x +2) (3x^{3} + 2x – x^{2} + 8) = 7x(3x^{3} + 2x – x^{2} + 8) + 2x
(3x^{3} + 2x – x^{2} + 8) = 21x^{4} + 14x^{2} – 7x^{3} + 56x + 6x^{3} + 4x – 2x^{2}+ 16 = 21x^{4} – x^{3} + 12x^{4} + 60x + 16
Question 4.
Let P(x) = 4x^{4} – 3x + 2x^{3} + 5 and q(x) = x^{2} + 2x + 4 find p (x) – q(x).
Solution:
Exercise 3.2
Question 1.
If p(x) = 5x^{3} – 3x^{2} + 7x – 9, find
(i) p(1)
(ii) p(2).
Solution:
Given that p(x) = 5x^{3} – 3x^{2} + 7x – 9
(i) p(1) = 5(1)^{3} – 3(1)^{2} + 7(1) – 9 = 5 – 3 – 7 – 9
= 24
(ii) p(2) = 5(2)^{3} – 3(2)^{3} + 7(2) – 9 = 40 – 12 + 14 – 9
∴ p(2) = 33
Question 2.
Find the zeros of the following polynomials.
(i) p(x) = 2x – 3
(ii) p(x) = x – 2
Solution:
Exercise 3.3
Question 1.
Find the remainder using remainder theorem, when
(i) 4x^{3} – 5x^{2} + 6x – 2 is divided by x – 1.
(ii) x^{3} – 7x^{2} – x + 6 is divided by x + 2.
Solution:
(i) Let p(x) = 4x^{3} – 5x^{2} + 6x – 2. The zero of (x – 1) is 1.
When p(x) is divided by (x – 1) the remainder is p( 1). Now,
p(1) = 4(1)^{3} – 5(1)^{2} + 6(1) – 2 = 4 – 5 + 6 – 2 = 3
∴ The remainder is 3.
(ii) Let p(x) = x^{3} – 7x^{2} – x + 6. The zero of x + 2 is 2.
When p(x) is divided by x + 2, the remainder is p(2). Now,
p(2) = (2)^{3} – 7(2)^{2} – (2) +6 = – 8 – 7(4) + 2 + 6
= – 8 – 28 + 2 + 6 = 28.
∴ The remainder is 28.
Question 2.
Find the value of a if 2x^{3} – 6x^{2} + 5ax – 9 leaves the remainder 13 when it is divided by x – 2.
Solution:
Let p(x) = 2x^{3} – 6x^{2} + 5ax – 9
When p(x) is divided by (x – 2) the remainder is p(2).
Given that p(2) = 13
⇒ 2(2)^{3} – 6(2)^{2} + 5a(2) – 9 = 13
⇒ 2(8) – 6(4) + 10a – 9 = 13
⇒ 16 – 24 + 10a – 9 = 13
⇒ 10a – 17 = 13
⇒ 10a = 30
⇒ ∴ a = 3
Question 3.
If the polynomials f(x) = ax^{3}+ 4x^{2} + 3x – 4 and g (x) = x^{3} – 4x + a leave the same remainder when divided by x – 3. Find the value of a. Also find the remainder.
Solution:
Let f(x) = ax^{3} + 4x^{2} + 3x – 4 and g(x) = x^{3} – 4x + a,When f(x) is divided by (x – 3), the remainder is f(3).
Now f(3) = a(3)^{3}4(3)^{2} + 3(3) – 4 = 27a + 36 + 9 – 4
f (3) = 27a + 41 …(1)
When g(x) is divided by (x – 3), the remainder is g(3).
Now g(3) = 33 – 4(3) + a = 27 – 12 + a = 15 + a …(2)
Since the remainders are same, (1) = (2)
Given that, f(3) = g(3)
That is 27a + 41 = 15 +a
27a – a = 15 – 41
26a = 26
Sustituting a = 1, in f(3), we get
f(3) = 27(1) + 41 = 27 + 41
f(3) = 14
∴ The remainder is 14.
Question 4.
Show that x + 4 is a factor of x^{3} + 6x^{2} – 7x – 60.
Solution:
Question 5.
In (5x + 4) a factor of 5x^{3} + 14x^{2} – 32x – 32
Solution:
Question 6.
Find the value of k, if (x – 3) is a factor of polynomial x^{3} – 9x^{2} + 26x + k.
Solution:
Let p (x) = x^{3} – 9x^{2} + 26x + k
By factor theorem, (x – 3) is a factor of p(x), if p(3) = 0
p(3) = 0
3^{3} – 9(3)^{2} + 26 (3) + k = 0
27 – 81 + 78 + k = 0
k = 24
Question 7.
Show that (x – 3) is a factor of x^{3} + 9x^{2} – x – 105.
Solution:
Let p(x) = x^{3} + 9x^{2} – x – 105
By factor theorem, x – 3 is a factor of p(x), if p(3) = 0
p (3) = 3^{3} + 9(3)^{3} – 3 – 105
= 27 + 81 – 3 – 105
= 108 – 108
p(3) = 0
Therefore, x – 3 is a factor of x^{3} + 9x^{2} – x – 105.
Question 8.
Show that (x + 2) is a factor of x^{3} – 4x^{2} – 2x + 20.
Solution:
Let p(x) = x^{3} – 4x^{2} – 2x + 20
By factor theorem,
(x + 2) is factor of p(x), if p(2) = 0
p(2) = (2)^{3} – 4(2)^{2} – 2(2) + 20 = 8 – 4(4) + 4 + 20
P( 2) = 0
Therefore, (x + 2) is a factor of x^{3} – 4x^{2} – 2x + 20
Exercise 3.4
Question 1.
Expand the following using identities :
(i) (7x + 2y)^{2}
(ii) (4m – 3m)^{2}
(iii) (4a + 3b) (4a – 3b)
(iv) (k + 2)(k – 3)
Solution:
(i) (7x + 2y)^{2} = (7x)^{2} + 2 (7x) (2y) + (2y)^{2} = 49x^{2} + 28xy + 4y^{2}
(ii) (4m – 3m)^{2} = (4m)^{2} – 2(4m) (3m) + (3m)^{2} = 16m^{2} – 24mn + 9n^{2}
(iii) (4a + 3b) (4a – 3b) [We have (a + b ) (a – b) = a^{2} – b^{2} ]
Put [a = 4a, b = 3b]
(4a + 3b) (4a – 3b) = (4a)^{2} – (3b)^{2} = 16a^{2} – 9b^{2}
(iv) (k + 2)(k – 3) [We have (x + a) (x – b) = x^{2} + (a – b)x – ab]
Put [x = k, a = 2, b = 3]
(k + 2) (k – 3) = k^{2} + (2 – 3)x – 2 × 3 = k^{2} – x – 6
Question 2.
Expand : (a + b – c)^{2}
Solution:
Replacing ‘c’ by ‘c’ in the expansion of
(a + b + c)^{2} = a^{2} + b^{2} + c^{2} + 2 ab+ 2 bc + 2ca
(a + b + (c))^{2} = a^{2} + b^{2} + (c)^{2} + 2ab + 2b(c) + 2(c)a
= a^{2} + b^{2} + c^{2} + 2ab – 2bc – 2ca
Question 3.
Expand : (x + 2y + 3z)^{2}
Solution:
We know that,
(a + b + c)^{2} = a^{2} + b^{2} + c^{2} + 2ab + 2bc + 2ca
Substituting, a = x, b = 2y and c = 3z
(x + 2y + 3 z)^{2} = x^{2} + (2y)^{2} + (3z)^{2} + 2(x)(2y) + 2(2y)(3z) + 2(3z)(x)
= x^{2} + 4y^{2} + 9z^{2} + 4xy + 12y^{2} + 6zx
Question 4.
Find the area of square whose side length is m + n – q.
Solution:
Area of square = side × side = (m + n – q)^{2}
We know that,
(a + b + c)^{2} = a^{2} + b^{2} + c^{2} + 2ab + 2bc + 2ca
[m + n + (q)]^{2} = m^{2} + n^{2} + (q)^{2} + 2mn + 2n(q) + 2(q)m
= m^{2} + n^{2} + q^{2} + 2mn – 2nq – 2qm
Therefore, Area of square = m^{2} + n^{2} + q^{2} + 2mn – 2nq – 2qm = [m^{2} + n^{2} + q^{2} + 2mn – 2nq – 2qm] sq. units.
EXERCISE 3.5
Question 1.
Factorise the following
(i) 25m^{2} – 16n^{2}
(ii) x^{4} – 9x^{2}
Solution:
(i) 25m^{2} – 16n^{2} = (5m)^{2} – (4n)^{2}
= (5m – 4n) (5m + 4n) [∵ a^{2} – b^{2} = (a – b)(a + b)]
(ii) x^{4} – 9x^{2} = x^{2}(x^{2} – 9) = x^{2}(x^{2} – 3^{2}) = x^{2}(x – 3)(x + 3)
Question 2.
Factorise the following.
(i) 64m^{3} + 27n^{3}
(ii) 729x^{3} – 343y^{3}
Solution:
(i) 64m^{3} + 27n^{3} = (4m)^{3} + (3n)^{3}
= (4m + 3n) ((4m)^{2} – (4m) (3n) + (3n)^{2}) [∵ a^{2} + b^{2} = (a + b) (a^{2} – ab + b^{2})]
= (4m + 3n) (16m^{2} – 12mn + 9n^{2})
(ii) 729x^{3} – 343y^{3} = (9x)^{3} – (7y)^{3} = (9x – 7y) ((9x)^{2} + (9x) (7y) + (7y)^{2}
= (9x – 7y) (81x^{2} + 63xy + 49y^{2})
[∵ a^{3} – b^{3} = (a – b) (a^{2} + ab + b^{2})]
Question 3.
Factorise 81x^{2} + 90x + 25
Solution:
81x^{2} + 90x + 25 = (9x)^{2} + 2 (9x) (5) + 5^{2}
= (9x + 5)^{2} [ ∵ a^{2} + 2ab + b^{2} = (a + b)^{2}]
Question 4.
Find a^{3} + b^{2} if a + b = 6, ab = 5.
Solution:
Given, a + b = 6, ab = 5
a^{2} + b^{2} = (a + b)^{2} – 3ab(a + b) = (6)^{3} – 3(5)(6) = 126
Question 5.
Factorise (a – b)^{2} + 7(a – b) + 10
Solution:
Let a – b = p, we get p^{2} + 7p + 10,
p^{2} + 7p + 10 = p^{2} + 5p + 2p + 10
= p(p + 5) + 2(p + 5) = (p + 5)(p + 2)
Put p = a – b we get,
(a – b)^{2} + 7(a – b) + 10 = (a – b + 5)(a – b + 2)
Question 6.
Factorise 6x^{2} + 17x + 12
Solution:
Exercise 3.6
Question 1.
Factorise x^{2} + 4x – 96
Solution:
Question 2.
Factorise x^{2} + 7xy – 12y^{2}
Solution:
Question 3.
Find the quotient and remainder when 5x^{3} – 9x^{2} + 10x + 2 is divided by x + 2 using synthetic division.
Solution:
Hence the quotient is 5x^{2} – 19x + 48 and remainder is 94.
Question 4.
Find the quotient and remainder when 7 + 3x – 2x^{2} + 5x^{3} is divided by 1 + 4x using synthetic division.
Solution:
Question 5.
If the quotient on dividing 5x^{4} + 4x^{3} + 2x + 1 by x + 3 is 5x^{3} + 9x^{2} + bx – 97 then find the values of a, b and also remainder.
Solution:
Quotient 5x^{3} + 11x^{2} + 33x – 97 is compared with given quotient 5x^{3} + ax^{2} + bx – 97
coefficient of x^{2} is – 11 = a and coefficient of x is 33 = b.
Therefore a = 11, b = 33 and remainder = 292.
Exercise 3.7
Question 1.
Find the quotient and the remainder when 10 – 4x + 3x^{2} is divided by x – 2.
Solution:
Let us first write the terms of each polynomial in descending order (or ascending
order). Thus the given problem becomes (3x^{2} – 4x + 10) ÷ (x – 2)
∴ Quotient = 3x + 2 and Remainder = 14, i.e 3x^{2} – 4x + 10 = (x – 2) (3x + 2) + 14 and is in the form
Dividend = (Divisor × Quotient) + Remainder
Question 2.
If 8x^{3} – 14x^{2} – 19x – 8 is divided by 4x + 3 then find the quotient and the remainder.
Solution:
Exercise 3.8
Question 1.
Factorise 2x^{3} – x^{2} – 12x – 9 into linear factors.
Solution:
Let p(x) = 2x^{3} – x^{2} – 12x – 9
Sum of the coefficients = 2 – 1 – 12 – 9 = 20 ≠ 0
Hence x – 1 is not a factor
Sum of coefficients of even powers with constant = 1 – 9 = 10
Sum of coefficients of odd powers = 2 – 12 = 10
Hence x + 1 is a factor of x.
Now we use synthetic division to find the other factors.
Then p (x) = (x + 1)(2x^{2} – 3x – 9)
Now 2x^{2} – 3x – 9 = 2x^{2} – 6x + 3x – 9 = 2x(x – 3) + 3(x – 3)
= (x – 3)(2x + 3)
Hence 2x^{3} – x^{2} – 12x – 9 = (x + 1) (x – 3) (2x + 3)
Question 2.
Factorize x^{3} + 3x^{2} – 13x – 15.
Solution:
Let p(x) = x^{3} + 3x^{2} – 13x – 15
Sum of all the coefficients = 1 + 3 – 13 – 15 = 24 + 0
Hence x – 1 is not a factor
Sum of coefficients of even powers with constant = 3 – 15 = – 12
Sum of coefficients of odd powers = 1 – 13 = – 12
Hence x + 1 is a factor of p (x)
Now use synthetic division to find the other factors.
Hence p(x) = (x + 1) (x^{2} + 2x – 15)
Now x^{3} + 3x^{2} – 13x – 15 = (x + 1)(x^{2} + 2x – 15)
Now x^{2} + 2x – 15 = x^{2} + 5x – 3x – 15 = x(x + 5) – 3 (x + 5) = (x + 5)(x – 3)
Hence x^{3} + 3x^{2} – 13x – 15 = (x + 1)(x + 5)(x – 3)
Question 3.
Factorize x^{3} + 13x^{2} + 32x + 20 into linear factors.
Solution:
Let, p(x) = x^{3} + 13x^{2} + 32x + 20
Sum of all the coefficients = 1 + 13 + 32 + 20 = 66 ≠ 0
Hence, (x – 1) is not a factor.
Sum of coefficients of even powers with constant = 13 + 20 = 33
Sum of coefficients of odd powers = 1 + 32 = 33
Hence, (x + 1) is a factor of p(x)
Now we use synthetic division to find the other factors
Exercise 3.9
Question 1.
Find GCD of 25x^{3}y^{2} z, 45x^{2}y^{4}z^{3}b
Solution:
Question 2.
Find the GCD of (y^{3} – 1) and (y – 1).
Solution:
y^{3} – 1 = (y – 1)(y^{3} + y + 1)
y – 1 = y – 1
Therefore, GCD = y – 1
Question 3.
Find the GCD of 3x^{2} – 48 and x^{2} – 7x + 12.
Solution:
3x^{2} – 48 = 3(x^{2} – 16) = 3(x^{2} – 4^{3}) = 3(x + 4)(x – 4)
x^{2} – 7x + 12 = x^{2} – 3x – 4x + 12 = x(x – 3) – 4 (x – 3) = (x – 3) (x – 4)
Therefore, GCD = x – 4
Question 4.
Find the GCD of a^{x} , a^{x + y}, a^{x + y + z}.
Solution:
Exercise 3.10
Question 5.
Solve graphically. x – y = 3 ; 2x – y = 11
Solution:
Exercise 3.11
Question 1.
Solve using the method of substitution. 5x – y = 5, 3x + y = 11
Solution:
Exercise 3.12
Question 2.
Solve by the method of elimination. 2x + y = 10; 5x – y = 11
Solution:
Exercise 3.13
Question 3.
Solve 5x – 2y = 10 ; 3x + y = 17 by the method of cross multiplication.
Solution:
Exercise 3.14
Question 1.
The age of Arjun is twice the sum of the ages of his two children. After 20 years, his age will be equal to the sum of the ages of his children. Find the age of the father.
Solution:
Let the age of the father be x
Let the sum of the age of his sons be y
At present x = 2y ⇒ x – 2y = 0 …. (1)
After 20 years x + 20 = y + 40
x – y = 40 – 20
Exercise 3.15
Multiple Choice Questions :
Question 1.
The polynomial 3x – 2 is a
(1) linear polynomial
(2) quadratic polynomial
(3) cubic polynomial
(4) constant polynomial
Hint: A polynomial is linear if its degree is 1
Solution:
(1) linear polynomial
Question 2.
The polynomial 4x^{2} + 2x – 2 is a
(1) linear polynomial
(2) quadratic polynomial
(3) cubic polynomial
(4) constant polynomial
Hint: A polynomial is quadratic of its highest power of x is 2
Solution:
(2) quadratic polynomial]
Question 3.
The zero of the polynomial 2x – 5 is
Hint:
Solution:
(1) 52
Question 4.
The root of the polynomial equation 3x – 1 = 0 is
Hint:
Solution:
(2) x = 13
Question 5.
Zero of (7 + 4x) is ___
Solution:
(2) −74
Question 6.
Which of the following has as a factor?
(1) x^{2} + 2x
(2) (x – 1)^{2}
(3) (x + 1)^{2}
(4) (x^{2} – 2^{2})
Solution:
(1) x^{2} + 2x
Question 7.
If x – 2 is a factor of q (x), then the remainder is _____
(1) q (2)
(2) x – 2
(3) 0
(4) 2
Solution:
(3) 0
Question 8.
(a – b) (a^{2} + ab + b^{2}) =
Solution:
(1) a^{3} + b^{3} + c^{3} – 3abc
(2) a^{2} – b^{2}
(3) a^{3} + b^{3}
(4) a^{3} – b^{3}
Solution:
(4) a^{3} – b^{3}
Question 9.
The polynomial whose factors are (x + 2) (x + 3) is
(1) x^{2} + 5x + 6
(2) x^{2} – 4
(3) x^{2} – 9
(4) x^{2} + 6x + 5
Solution:
(1) x^{2} + 5x + 6
Question 10.
(a – b – c)^{2} is equal to
(1) (a – b + c)^{2}
(2) (a + b – c)^{2}
(3) (a + b + c)^{2}
(4) (a + b + c)^{2}
Solution:
(4) (a + b + c)^{2}
Text Book Activities
Activity – 1
Write the Variable, Coefficient and Constant in the given algebraic expression,
Solution:
Activity – 2
Write the following polynomials in standard form.
Activity – 3
Question 1.
Find the value of k for the given system of linear equations satisfying the condition below:
(i) 2x + ky = 1; 3x – 5y = 7 has a unique solution
(ii) kx + 3y = 3; 12x + ky = 6 has no solution
(iii) (k – 3)x + 3y = k; kx + ky = 12 has infinite number of solution
Solution:
Question 2.
Find the value of a and b for which the given system of linear equation has infinite number of solutions 3x – (a + 1)y = 2b – 1, 5x + (1 – 2a)y = 3b
Solution:
Activity – 4
For the given linear equations, find another linear equation satisfying each of the given condition
Solution:
How to Prepare using Samacheer Kalvi 9th Maths Chapter 3 Algebra Notes PDF?
Students must prepare for the upcoming exams from Samacheer Kalvi 9th Maths Chapter 3 Algebra Notes PDF by following certain essential steps which are provided below.
 Use Samacheer Kalvi 9th Maths Chapter 3 Algebra notes by paying attention to facts and ideas.
 Pay attention to the important topics
 Refer TN Board books as well as the books recommended.
 Correctly follow the notes to reduce the number of questions being answered in the exam incorrectly
 Highlight and explain the concepts in details.
Samacheer Kalvi 9th Maths All Chapter Notes PDF Download
 Samacheer Kalvi 9th Maths Chapter 1 Set Language Notes PDF Download: Tamil Nadu STD 9th Maths Chapter 1 Set Language Notes
 Samacheer Kalvi 9th Maths Chapter 2 Real Numbers Notes PDF Download: Tamil Nadu STD 9th Maths Chapter 2 Real Numbers Notes
 Samacheer Kalvi 9th Maths Chapter 3 Algebra Notes PDF Download: Tamil Nadu STD 9th Maths Chapter 3 Algebra Notes
 Samacheer Kalvi 9th Maths Chapter 4 Geometry Notes PDF Download: Tamil Nadu STD 9th Maths Chapter 4 Geometry Notes
 Samacheer Kalvi 9th Maths Chapter 5 Coordinate Geometry Notes PDF Download: Tamil Nadu STD 9th Maths Chapter 5 Coordinate Geometry Notes
 Samacheer Kalvi 9th Maths Chapter 6 Trigonometry Notes PDF Download: Tamil Nadu STD 9th Maths Chapter 6 Trigonometry Notes
 Samacheer Kalvi 9th Maths Chapter 7 Mensuration Notes PDF Download: Tamil Nadu STD 9th Maths Chapter 7 Mensuration Notes
 Samacheer Kalvi 9th Maths Chapter 8 Statistics Notes PDF Download: Tamil Nadu STD 9th Maths Chapter 8 Statistics Notes
 Samacheer Kalvi 9th Maths Chapter 9 Probability Notes PDF Download: Tamil Nadu STD 9th Maths Chapter 9 Probability Notes
0 comments:
Post a Comment